2000
DOI: 10.1038/sj.cdd.4400690
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of phosphatidylserine on macrophages is required for phagocytosis of apoptotic thymocytes

Abstract: Cells generally maintain an asymmetric distribution of phospholipids across the plasma membrane bilayer, restricting the phospholipid, phosphatidylserine (PS), to the inner leaflet of the plasma membrane. When cells undergo apoptosis, this asymmetric transbilayer distribution is lost, bringing PS to the surface where it acts as a signal for engulfment by phagocytes. The fluorescent dye merocyanine 540 specifically stains the plasma membrane of apoptotic cells which have lost their asymmetric distribution of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
134
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 46 publications
5
134
1
1
Order By: Relevance
“…It will be interesting to examine whether any other molecules work as phosphatidylserine receptors. Some non-apoptotic T or B cells 25,26 as well as macrophages 27 have been reported to bind annexin V. Here, we showed that the cells expressing Tim1 or Tim4 associated with exosomes that carried exposed PS. Activated Th2 cells and B cells express Tim1 28,29 , while the resident macrophages express Tim4, suggesting that the nonapoptotic annexin V-binding cells are those that express Tim1 or Tim4.…”
mentioning
confidence: 53%
“…It will be interesting to examine whether any other molecules work as phosphatidylserine receptors. Some non-apoptotic T or B cells 25,26 as well as macrophages 27 have been reported to bind annexin V. Here, we showed that the cells expressing Tim1 or Tim4 associated with exosomes that carried exposed PS. Activated Th2 cells and B cells express Tim1 28,29 , while the resident macrophages express Tim4, suggesting that the nonapoptotic annexin V-binding cells are those that express Tim1 or Tim4.…”
mentioning
confidence: 53%
“…67 This PS exposed on the phagocyte surface is required in the phagocytosis process, since treating macrophages with annexin is as effective as treating apoptotic lymphocytes in blocking the engulfment process. 84 The engulfment process thus seems to require interactions between PS-exposing membranes on both the engulfing and target cells, interactions that are not required for engulfment of other, non-PS-exposing particles by the same phagocytes.…”
Section: Cell Death and Differentiationmentioning
confidence: 99%
“…For annexin V staining, cells were resuspended in annexin V staining buffer (10 mM HEPES/NaOH, pH 7.4, 140 mM NaCl, 2.5 mM CaCl 2 ) before staining with PE-conjugated annexin V (BD PharMingen). Propidium iodide was added before flow cytometry to gate out dead cells (19). As negative controls for all annexin V staining, cells were extensively washed in Ca 2ϩ -free PBS before adding annexin V.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Following HIV-1 infection, T cells are highly susceptible to programmed cell death, and peak levels of T cell apoptosis correlate with high levels of virus replication (18). Furthermore, mature macrophages constitutively express PS in the outer leaflet of their plasma membranes (19), although their precursors, monocytes, do not (20). Therefore, HIVinfected T cells and macrophages would be expected to have elevated levels of surface PS, and HIV-1 particles produced by these cells would have PS incorporated into the outer leaflet of their envelopes.…”
mentioning
confidence: 99%